Analisis Produksi Program AB TV News di PT. Astro Blitar TV - Monicha, Denty; Kusumawijayanti, Anita Reta; Nuryanti, Nuryanti (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2023)
News programs become a special identity of television stations. Its also one of the responsibility of the media to give information, education and entertainment to the society. ABTV News is a regular news program presented by PT. Astro Blitar Television, one of the local TV stations in Blitar Regency, East Java. This methodology used is a descriptive qualitative approach. Data collection is through interview, observation, and documentation. The result was conluded that production process on television have Standard Operational Procedure (SOP) namely pre-production, production and post-production. That are in accordance with the SOP for the ABTV News program production process. Pre-production on the ABTV News program begins with finding idea or information, planning, and preparation. As for the production process, consists of news coverage, followed by script writing. Post-production is the final stage in the process production of the ABTV News program.